(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Uzbekistan, a country rich in natural resources and cultural heritage, has been undergoing significant economic and political transformations in recent years. As the country strives to achieve sustainable and inclusive growth, the role of sustainable and green financing has become increasingly crucial. This article will explore the concept of sustainable and green financing, its importance in Uzbekistan, and the opportunities and challenges that lie ahead